A STRATEGY FOR SUSTAINABLE WASTE MANAGEMENT IN OIL AND GAS INDUSTRY - Dwi Anggoro Ismukurnianto (Testing Center for Oil and Gas LEMIGAS, 2003)
Oil and gas industries unavoidably generate huge quantity of waste during their activities including exploration, production, storage, gathering, processing, transmission, distribution or combination of these.